The Effect of the Snakes and Ladders Educational Game on Students' Interpersonal Intelligence in Social Studies Learning at SMP Negeri 2 Pamanukan, Subang Regency - Indah Kristina Wulandari; Lili Halimah; Eneng Martini (EDUKASI, 2026)
This study aims to examine the effect of the educational snakes and ladders game on students’ interpersonal intelligence in Social Studies learning and to explain how the game implementation facilitates communication, collaboration, and empathy during classroom activities. The research employed a mixed methods approach with a sequential explanatory design. The quantitative phase involved 245 students selected from a population of 629 students at SMP Negeri 2 Pamanukan, Subang Regency, using the Slovin formula. Data were collected through Likert-scale questionnaires and analyzed PLS-SEM to evaluate the measurement model and structural model. The results indicate that the educational snakes and ladders game has a positive and significant effect on interpersonal intelligence, with a path coefficient of 0.730 (p < 0.05) and an R-square value of 0.532, indicating substantial explanatory power. The game also significantly influences communication (0.661; R² = 0.437), collaboration (0.714; R² = 0.510), and empathy (0.605; R² = 0.366) as core indicators of interpersonal intelligence. The qualitative phase, conducted through classroom observations and interviews with teachers and students, supports the quantitative findings by showing that the game creates an interactive, participatory, and collaborative learning environment that naturally encourages social interaction. These findings demonstrate that the snakes and ladders game is not merely an instructional aid but functions as a pedagogical strategy capable of strengthening students’ interpersonal intelligence in Social Studies learning. This study contributes empirically and conceptually to the development of game-based learning oriented toward social competence.